The 24 Aqr triple system: A closer look at its unique high-eccentricity hierarchical architecture - Abushattal, Ahmad A.; Al-Wardat, Mashhoor A.; Horch, Elliott P.; Georgakarakos, Nikolaos; Al-Ameryeen, Hatem A.; Abu-Alrob, Enas M.; Hussein, Abdallah M. (Advances in Space Research, 2023)
As its periastron passage occurred during the third quarter of 2020, system 24 Aqr is of particular significance. New visual solutions for the latest speckle interferometry observations collected by the Lowell Discovery Telescope (LTD) with its new QWSSI speckle camera are presented here. A variety of techniques were used to analyze the system, including ORBITX code for orbital solution, Al-Wardat’s method for analyzing multiple stellar systems, and Edwards’ method for analyzing visual and spectroscopic binaries. We derive precise masses and the complete set of its fundamental parameters for the three components, and we introduce a new orbital solution, and a new dynamical parallax, which is very close to the measured value given by Hipparcos 2007 and from that of Gaia DR2. In the next section, we discuss the possibility of a coplanar orbit. In conclusion, we demonstrate that we need a 65-m telescope to resolve the inner binary visually, although an array of telescopes could be used instead.
Keywords: Atmospheric Modeling-Synthetic Photometry; Hierarchical Triple System; Multiple stars; Observational Astronomy; Spectroscopic Binary Stars; Stars: binaries: close; Visual Binary Stars; dept.phy; peer-reviewed